Higiene Santasi Makanan Di Kantin Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia Makassar - Fahrunnisa S, Nurul; Nur Ulmy Mahmud; Ulfa Sulaeman (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Hygiene and sanitation in food processing need to be considered to prevent bacterial contamination that will damage the quality of food. The role of sanitation is crucial to prevent the growth and development of spoilage microbes in food, drinks, or equipment that can damage food and endanger humans. One of the principles of food sanitation hygiene that needs to be considered is the hygiene and sanitation of eating utensils. The canteen is at risk of becoming a place for the spread of all diseases with food and drink media that have the potential to cause foodborne diseases if not managed properly. Problems that often arise in the canteen include building factors, construction, and sanitation facilities. In addition, it is related to the personal hygiene of food handlers. This type of research uses a descriptive cross-sectional research approach, namely examining the number of germs using the Total Plate Count (ALT) method by measuring the parameters of the number of germs on trader equipment in the canteen of the Faculty of Public Health, Muslim University of Indonesia. The results of the study obtained that the assessment of food sanitation hygiene observations in the canteen (20%) met the requirements and (80%) did not meet the requirements in accordance with the requirements for the suitability of food sanitation hygiene that has been set by Permenkes No.1096.Menkes/PER/VI/2011. The examination results of the number of germs on 30 eating and drinking utensils (100%) did not meet the requirements, with a total of 1046 CFU/cm3, indicating a high level of contamination. From this study, the researcher suggests that traders or food handlers in the canteen remember the importance of paying attention to and improving the hygiene and sanitation of eating utensils to maintain the quality of equipment sanitation in order to produce healthy and consumable food and maintain personal hygiene through behavior and actions so that food is not contaminated.